1993
DOI: 10.1152/jn.1993.69.5.1684
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous sensory receptors in the rat foot

Abstract: 1. A total of 574 cutaneous afferent units in the sural and plantar nerves supplying the skin of the rat foot was examined: 399 A beta-units, 55 A delta-units, and 120 C-units. Their receptive-field (RF) properties were similar to those described in other mammals. However, the receptor type composition of units was different between the two nerves. 2. The sural A beta-fiber sample (n = 160) consisted of G-hair (41%), field (11%), rapidly adapting (RA; 6%), slowly adapting type I (SA-I; 7%), and type II (SA-II;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
250
5

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(283 citation statements)
references
References 0 publications
28
250
5
Order By: Relevance
“…When we recorded from single fibers ( figure 4C), the CV of the uninjured segment was well within this range for Aβ fibers (Feasby et al, 1981,Shin et al, 1997. The regenerated axon segments did not conduct slower than 2m/sec, the upper CV of C-fibers (Leem et al 1993) and these axon segments were able to follow reliably at stimulation frequencies of up to 10 Hz, a frequency at which C-fibers show conduction changes (Koga et al 2005). Since we stimulated regenerated fibers at spinal level T9, it is also unlikely that the fibers were displaced Ia afferents that normally terminate in Clarke's column.…”
Section: Discussionmentioning
confidence: 60%
“…When we recorded from single fibers ( figure 4C), the CV of the uninjured segment was well within this range for Aβ fibers (Feasby et al, 1981,Shin et al, 1997. The regenerated axon segments did not conduct slower than 2m/sec, the upper CV of C-fibers (Leem et al 1993) and these axon segments were able to follow reliably at stimulation frequencies of up to 10 Hz, a frequency at which C-fibers show conduction changes (Koga et al 2005). Since we stimulated regenerated fibers at spinal level T9, it is also unlikely that the fibers were displaced Ia afferents that normally terminate in Clarke's column.…”
Section: Discussionmentioning
confidence: 60%
“…EC has been used previously in behavioral studies, and similar temperature changes have been reported (Hao et al, 1996(Hao et al, , 1999Sjolund et al, 1998). These temperature changes are sufficiently cold to activate populations of nociceptive afferents (LaMotte and Thalhammer, 1982;Lynn and Carpenter, 1982;Leem et al, 1993;Kajander, 1996, 1997). However, temperatures reported to produce cold pain sensation in humans and nociceptive behaviors in animals are highly variable, likely due to the wide variety of stimuli used and responses measured, making comparison between studies difficult.…”
Section: Neural Mechanisms Of Cold Somatosensationmentioning
confidence: 76%
“…Innocuous cooling activates subsets of A␦-and C-fiber lowthreshold afferents (Bessou and Perl, 1969;Leem et al, 1993;Campero et al, 1996). More intense cold stimuli additionally activate populations of nociceptive afferents (both A␦-and C-fiber units), which display a range of activation thresholds and encode changes in stimulus intensity (LaMotte and Thalhammer, 1982;Lynn and Carpenter, 1982;Leem et al, 1993;Kajander, 1996, 1997;Cain et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A change of movement pattern would produce a corresponding change in the sensory feedback that ensues on muscle contraction, because the feedback from most cutaneous mechanoreceptors reflects the change in load on the skin surface (Fleischer et al, 1983;Willis and Coggeshall, 1991;Leem et al, 1993). The change of receptive fields corresponded to the induced changes of the movement patterns of the manipulated muscles.…”
Section: Mechanisms Underlying the Postnatal Tuning Of Withdrawal Refmentioning
confidence: 99%